2018
DOI: 10.1007/s12602-018-9443-6
|View full text |Cite
|
Sign up to set email alerts
|

Supportive Role of Probiotic Strains in Protecting Rats from Ovariectomy-Induced Cortical Bone Loss

Abstract: Osteoporosis is a major health problem that occurs as a result of an imbalance between bone formation and bone resorption. Different approaches have been established for treating osteoporosis. Recently, because of their health benefits and also low adverse reaction, probiotics have been receiving considerable attention. In this study, we compared the effectiveness of five probiotic strains, Lactobacillus acidophilus, Lactobacillus reuteri, Lactobacillus casei, Bifidobacterium longum, and Bacillus coagulans, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(87 citation statements)
references
References 36 publications
11
76
0
Order By: Relevance
“…(121) In addition to altering the gut microbiome and reducing intestinal inflammation, probiotics are known to promote intestinal barrier function and benefit bone health. (50,(53)(54)(55)(56)(57)63,67,68,71,73,75,76,(122)(123)(124)(125)(126)(127)(128)(129)(130)(131)(132) Consistent with these studies, we found that treatment with LR as well as LGG uniquely altered the microbiota composition, which was significantly different from mice treated with GC alone. We hypothesize that each of these compositions have a different balance of healthy versus disease-promoting bacteria, which could be playing a role in its differential effects on the intestinal barrier and furthermore bone health.…”
Section: Discussionsupporting
confidence: 85%
“…(121) In addition to altering the gut microbiome and reducing intestinal inflammation, probiotics are known to promote intestinal barrier function and benefit bone health. (50,(53)(54)(55)(56)(57)63,67,68,71,73,75,76,(122)(123)(124)(125)(126)(127)(128)(129)(130)(131)(132) Consistent with these studies, we found that treatment with LR as well as LGG uniquely altered the microbiota composition, which was significantly different from mice treated with GC alone. We hypothesize that each of these compositions have a different balance of healthy versus disease-promoting bacteria, which could be playing a role in its differential effects on the intestinal barrier and furthermore bone health.…”
Section: Discussionsupporting
confidence: 85%
“…For example, whether vitamin D supplementation should be considered in African countries to reduce vaginal L. iners or rise L. crispatus , as was tried recently in a pregnant cohort (Jefferson et al, 2019). Gut probiotics such as L. casei , B. longum have been reported to increase vitamin D in ovariectomy-induced mice model of osteoporosis (Montazeri-Najafabady et al, 2018), and our results suggest that there might be counterparts in the female reproductive tract after getting married and pregnant.…”
Section: Discussionsupporting
confidence: 52%
“…The probiotics were isolated from traditional fermented dairy products, produced in Iran according to Montazeri et al (16). Brie y, 10 g of each dairy samples was homogenized, serially diluted and cultured on TSA medium.…”
Section: Bacterial Isolation and Formulationmentioning
confidence: 99%
“…It is supposed that their bene cial effect is related to many internal mechanisms including the skeletal system beyond control of blood glucose (15). In a preceding study, we reported that some types of probiotics could improve the bone formation, reduced bone resorption, and changes in the microstructure of the femur in ovariectomized-induced bone loss rat model (16,17). Dar et al disclosed that administration of lactobacillus acidophilus for 12 weeks could attenuate the bone loss and improve the mechanical bone strength in streptozotocin-induced diabetic rats with no impacts on glucose concentration (18).…”
mentioning
confidence: 97%